Issues and lessons learned in registering restaurant business into Google Business and online food delivery platforms in Indonesia - Arif Wibisono; Rully Agus Hendrawan; Amna Shifia Nisafani; Mahendrawathi ER; Erma Suryani; Andre Parvian Aristio (Sewagati, 2018)
Online food delivery (OFD) has changed how a restaurant business promote itself. Not only to improve its presences on the mobile internet but also to open an unprecedented sales ordering channel(s). This study aims to highlight issues and lessons learned during our efforts to register various restaurant business in online food delivery setting. We have registered as many as 12 restaurant businesses in Surabaya into both Go Food and Grab Food platforms. Here, Go Food and Grab Food are two leading providers for food deliver platform in Indonesia. Along with OFD, we also register those companies into Google Platform which is the largest business listing worldwide. Both OFD and Google Platform are intended to enhance sales performances. This study outlines the imposed procedures of the two platforms and examines the bottleneck points. Also, we gauge any potential issues from restaurant owners to satisfy the platform’s requirements. Later, we make a matrix that lists all arising problems that slack the registration processes. In the end of the study, we have found that business owner distrust is the major obstacle to incorporate his/her business into a food delivery app platform.